Design of Teaching Materials Based on Science, Technology, Engineering and Mathematics Pencak Silat Material in Junior High Schools - Handayani, Anastasyia; Usra, Meirizal; Bayu, Wahyu Indra; Hartati, Hartati; Yusfi, Herri; Syafaruddin, Syafaruddin (Bravo's : Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2023)
Education is a person's effort to develop their personality in accordance with the values of society and culture. In learning pencak silat, students will be taught basic movements, self-defense techniques, and the art of pencak silat. To help develop themselves better, students must keep up with the times so that they have more freedom to develop themselves. In the STEM (Science, Technology, Engineering and Mathematics) learning model with an educational approach that combines science, technology, engineering and mathematics in an integrated learning environment. STEM learning is very good if applied to PJOK learning, especially in pencak silat material. This research was conducted to apply teaching materials designed on a STEM basis in PJOK subjects with pencak silat material at SMP Negeri 19 Palembang. This research is an experimental study of The Equivalent Time Series Sample during 4 weeks of meetings which was measured using LKPD (Learner Worksheets) and FCE (Formative Class Evaluation) questionnaires. The samples used were students in class 7.11 at SMP Negeri 19 Palembang, totaling 30 students. The results of the research carried out were: 1) LKPD showed results in the poor category. 2) The FCE questionnaire shows results in the medium category. So it can be concluded that there is a difference between learning pencak silat using STEM and not using STEM.